Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Connect with professionals ready to provide precise answers to your questions on our comprehensive Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Let’s solve the given problem step-by-step:
1. Given: [tex]\(\sin A = \frac{3}{5}\)[/tex]
2. Find [tex]\(\cos A\)[/tex]:
We know that [tex]\(\sin^2 A + \cos^2 A = 1\)[/tex]. Therefore, we can use the Pythagorean identity to find [tex]\(\cos A\)[/tex]:
[tex]\[ \sin^2 A + \cos^2 A = 1 \\ \left(\frac{3}{5}\right)^2 + \cos^2 A = 1 \\ \frac{9}{25} + \cos^2 A = 1 \\ \cos^2 A = 1 - \frac{9}{25} \\ \cos^2 A = \frac{25}{25} - \frac{9}{25} \\ \cos^2 A = \frac{16}{25} \\ \cos A = \sqrt{\frac{16}{25}} \\ \cos A = \frac{4}{5} \][/tex]
We chose the positive root since cosine in the first quadrant (where sine is positive) is also positive.
3. Calculate [tex]\(\tan A\)[/tex]:
We know that [tex]\(\tan A = \frac{\sin A}{\cos A}\)[/tex]:
[tex]\[ \tan A = \frac{\frac{3}{5}}{\frac{4}{5}} \\ \tan A = \frac{3}{5} \times \frac{5}{4} \\ \tan A = \frac{3}{4} \][/tex]
4. Use the double-angle formula for [tex]\(\tan(2A)\)[/tex]:
The double-angle formula for tangent is given by:
[tex]\[ \tan(2A) = \frac{2 \tan A}{1 - \tan^2 A} \][/tex]
Substitute [tex]\(\tan A = \frac{3}{4}\)[/tex]:
[tex]\[ \tan(2A) = \frac{2 \times \frac{3}{4}}{1 - \left(\frac{3}{4}\right)^2} \\ \tan(2A) = \frac{\frac{6}{4}}{1 - \frac{9}{16}} \\ \tan(2A) = \frac{\frac{6}{4}}{\frac{16}{16} - \frac{9}{16}} \\ \tan(2A) = \frac{\frac{6}{4}}{\frac{7}{16}} \\ \tan(2A) = \frac{6}{4} \times \frac{16}{7} \\ \tan(2A) = \frac{6 \times 16}{4 \times 7} \\ \tan(2A) = \frac{96}{28} \\ \tan(2A) = \frac{24}{7} \][/tex]
5. Determine [tex]\(-\tan(2A)\)[/tex]:
Since the problem asks for [tex]\(-\tan(2A)\)[/tex]:
[tex]\[ -\tan(2A) = -\frac{24}{7} \][/tex]
Thus, we have shown that if [tex]\(\sin A = \frac{3}{5}\)[/tex], then [tex]\(-\tan 2A = -\frac{24}{7}\)[/tex].
1. Given: [tex]\(\sin A = \frac{3}{5}\)[/tex]
2. Find [tex]\(\cos A\)[/tex]:
We know that [tex]\(\sin^2 A + \cos^2 A = 1\)[/tex]. Therefore, we can use the Pythagorean identity to find [tex]\(\cos A\)[/tex]:
[tex]\[ \sin^2 A + \cos^2 A = 1 \\ \left(\frac{3}{5}\right)^2 + \cos^2 A = 1 \\ \frac{9}{25} + \cos^2 A = 1 \\ \cos^2 A = 1 - \frac{9}{25} \\ \cos^2 A = \frac{25}{25} - \frac{9}{25} \\ \cos^2 A = \frac{16}{25} \\ \cos A = \sqrt{\frac{16}{25}} \\ \cos A = \frac{4}{5} \][/tex]
We chose the positive root since cosine in the first quadrant (where sine is positive) is also positive.
3. Calculate [tex]\(\tan A\)[/tex]:
We know that [tex]\(\tan A = \frac{\sin A}{\cos A}\)[/tex]:
[tex]\[ \tan A = \frac{\frac{3}{5}}{\frac{4}{5}} \\ \tan A = \frac{3}{5} \times \frac{5}{4} \\ \tan A = \frac{3}{4} \][/tex]
4. Use the double-angle formula for [tex]\(\tan(2A)\)[/tex]:
The double-angle formula for tangent is given by:
[tex]\[ \tan(2A) = \frac{2 \tan A}{1 - \tan^2 A} \][/tex]
Substitute [tex]\(\tan A = \frac{3}{4}\)[/tex]:
[tex]\[ \tan(2A) = \frac{2 \times \frac{3}{4}}{1 - \left(\frac{3}{4}\right)^2} \\ \tan(2A) = \frac{\frac{6}{4}}{1 - \frac{9}{16}} \\ \tan(2A) = \frac{\frac{6}{4}}{\frac{16}{16} - \frac{9}{16}} \\ \tan(2A) = \frac{\frac{6}{4}}{\frac{7}{16}} \\ \tan(2A) = \frac{6}{4} \times \frac{16}{7} \\ \tan(2A) = \frac{6 \times 16}{4 \times 7} \\ \tan(2A) = \frac{96}{28} \\ \tan(2A) = \frac{24}{7} \][/tex]
5. Determine [tex]\(-\tan(2A)\)[/tex]:
Since the problem asks for [tex]\(-\tan(2A)\)[/tex]:
[tex]\[ -\tan(2A) = -\frac{24}{7} \][/tex]
Thus, we have shown that if [tex]\(\sin A = \frac{3}{5}\)[/tex], then [tex]\(-\tan 2A = -\frac{24}{7}\)[/tex].
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.